2018
DOI: 10.29252/nirp.jpcp.6.1.9
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Self-Compassion and Self-Esteem Based on Their Relationship With Adaptive and Maladaptive Emotion Regulation Strategies

Abstract: Objective: The purpose of this study was to investigate the relationship between adaptive and maladaptive cognitive emotion regulation strategies, self-compassion, and self-esteem; and to determine whether self-compassion compared to self-esteem, was a better predictor of the scores on the adaptive and maladaptive cognitive emotion regulation strategies.Methods: This was a cross-sectional study. The statistical population included all students of the University of Applied Science and Technology (unit 47 in Teh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The results showed that general positive reactivity, positive-duration, positive-activation, and positive-intensity had a positive and significant correlation with self-compassion, self-esteem, and eating selfefficacy. Based on the results, general negative reactivity, negative-duration, negative-activation, and negativeintensity showed a negative and significant correlation with self-compassion (45,46), self-esteem (47,48) and eating self-efficacy (49,50). High negative reactivity and low positive reactivity are associated with psychopathology (6).…”
Section: Discussionmentioning
confidence: 92%
“…The results showed that general positive reactivity, positive-duration, positive-activation, and positive-intensity had a positive and significant correlation with self-compassion, self-esteem, and eating selfefficacy. Based on the results, general negative reactivity, negative-duration, negative-activation, and negativeintensity showed a negative and significant correlation with self-compassion (45,46), self-esteem (47,48) and eating self-efficacy (49,50). High negative reactivity and low positive reactivity are associated with psychopathology (6).…”
Section: Discussionmentioning
confidence: 92%
“…Many psychological theories proclaim how the pursuit of maintaining positive emotions, including high self-esteem, can lead to cognitive biases and distortions, self-deception, or favoritism. In contrast, self-compassion offers little incentive for false beliefs and defensiveness, since accepting our weak points is portrayed as a success rather than failure [28]. Hence, self-compassion could potentially co-op the position of self-esteem in the theoretical and empirical discourse regarding mental health.…”
Section: Self-compassionmentioning
confidence: 96%